Design and development of android application of bernoulli equation ebook and calculator - Mohammad Shahidil Saffuan, Rosli (2012)
This thesis deals with the android software application which is use in the android Smartphone and Tablets. The objective of this thesis is to design and develop an android software application of Bernoulli equation EBook and calculator. The process uses to design and develop this software application is the MIT AppInventor. The MIT AppInventor is originally provided by Google and now maintained by Massachusetts Institute of Technology (MIT). Bernoulli equation is the subtopic of the fluid mechanics study which is the core subject for the mechanical engineering students. The application provided all the notes of the Bernoulli equation which contains the introduction, derivation, Torricelli’s theorem, HGL and EGL, type of pressure involved, limitation of Bernoulli equation. Furthermore, it is also contain a few question involved in Application of Bernoulli equation. All the questions being provide with the manual solution. Besides that, this application also contains the universal calculator for Bernoulli equation. This will give easier for the students to calculate the Bernoulli equation. They just need to identify the value all the variables of the question and use this application to key in the value and the application will automatically calculate. All the syllabus of the Bernoulli equation contains in this application is provided for Diploma of Mechanical engineering students. Survey has been done at University Malaysia Pahang involved in 50 students and 20 lecturers before the Bernoulli equation application are released.